Phenomenography for researching aspects of networked learning: Beyond the match of underlying values and beliefs - Cutajar, Maria (Proceedings of the International Conference on Networked Learning, 2014)
Networked learning as a pedagogical approach aims to advance technology mediated learning through relations with resources, tutors and students. Phenomenography is a qualitative research approach concerned with revealing patterns of variation in the relations between human beings and aspects of the world around them. Phenomenography and networked learning attend to different functions in different fields of operation - the former on doing research about learning and the latter on begetting students' learning, but both advance a relational view of learning. This short paper is the outcome of a reflective enquiry when personally engaged doing phenomenographic research exploring variation in the student's lived experience of networked learning. With it I seek to draw attention to a perceived set of values and beliefs shared by, and underpinning both approaches. I claim to underline the advantage of a foundational ground shared by phenomenography and networked learning, also suggesting philosophical coherence and continuity when the human actor operating in the networked learning field shifts to the phenomenographic field. However, the advantage of phenomenography to research the networked learning field is perceived to go beyond shared philosophical ground and related methodological accord. In its capacity to explicitly reveal open patterns of variation in person-world relationships phenomenography is envisaged to potentially be an empowering means of learning and for learning. Perhaps, an in-depth study looking into the points of convergence and divergence when using phenomenography to investigate aspects of networked learning may help clarify conjectures at the abstract level and beyond this, on a more practical note, it may help to better highlight capabilities, limitations, facilitations and pitfalls, thus illuminating prospects for those who contemplate phenomenography to understand and promote networked learning. Structurally, the paper is subdivided into three sections. The first section highlights networked learning as a relational approach distinct from other similar technology-mediated learning strategies such as connectivism and computer supported collaborative learning. The second section briefly outlines the main paradigmatic features of phenomenography characterised by the person-phenomenon relationship advancing learning as expanding consciousness. The third section calls attention to three issues whereupon the phenomenographic stance appears to match the networked learning approach, these being that, both steer clear of dualisms, contemplate learning at the nexus of relations, and emphasise the value and agency of human beings, individually and collectively.